1992
DOI: 10.1128/aem.58.1.233-236.1992
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Fumonisin B 1 in Naturally Contaminated Corn during Ethanol Fermentation

Abstract: Two lots of corn naturally contaminated with fumonisin B1 (15 and 36 ppm) and a control lot (no fumonisin B1 detected) were used as substrates for ethanol production in replicate 8.5-liter yeast fermentations. Ethanol yields were 8.8% for both the control and low-fumonisin corn, while the high-fumonisin corn contained less starch and produced 7.2% ethanol. Little degradation of fumonisin occurred during fermentation, and most was recovered in the distillers' grains, thin stillage, and distillers' solubles frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 21 publications
4
41
1
Order By: Relevance
“…To date no study of the brewing process with regard to carryover of fumonisins into beer has been carried out. However, yeast fermentation of fumonisin B 1 -contaminated corn used as a substrate for ethanol production showed little degradation of the fumonisin 19 . Of the initial fumonisin B 1 , 31-35% was recovered in the distillers' dried grains, which actually had increased concentrations of fumonisin B 1 , whereas 51-54% was extracted into the whole stillage.…”
Section: Mycotoxins In Cerealsmentioning
confidence: 99%
“…To date no study of the brewing process with regard to carryover of fumonisins into beer has been carried out. However, yeast fermentation of fumonisin B 1 -contaminated corn used as a substrate for ethanol production showed little degradation of the fumonisin 19 . Of the initial fumonisin B 1 , 31-35% was recovered in the distillers' dried grains, which actually had increased concentrations of fumonisin B 1 , whereas 51-54% was extracted into the whole stillage.…”
Section: Mycotoxins In Cerealsmentioning
confidence: 99%
“…43 The temperature and pH level of alcohol fermentation have been reported as having a limited effect on fumonisin content. 44 Fumonisins are comparatively heat stable and significant elimination only occurs during processes in excess of 150 ∘ C. It has been revealed that the type of cooking process significantly affects the temperature required to achieve a reduction of more than 50% in fumonisin content: 190 ∘ C for frying of corn chips; 45 160 ∘ C for extrusion of corn grits; 46 218 ∘ C for roasting corn meal. 47 Cooking time also affects the stability of fumonisins.…”
Section: Fumonisinsmentioning
confidence: 99%
“…Although this is the first report on the potential effects of Stenocarpella rotted corn on yeast fermentation, prior results have been published regarding ethanol fermentations that used corn naturally infected with Aspergillus flavus and contaminated with aflatoxin (Lillehoj et al 1978;Bothast et al 1982) and corn naturally contaminated with fumonisin B 1 (Bothast et al 1992) or zearalenone (Bennett et al 1981). The primary objective of these studies was to determine the fate of mycotoxins during the ethanol fermentation.…”
Section: Effect Of Ear Rot Infection On Ethanol Fermentation and Ddgsmentioning
confidence: 99%
“…Corn ethanol producers carefully grade corn that enters their facilities and are particularly careful in regard to fungal-damaged corn, because corn contaminated with mycotoxins becomes concentrated threefold in DDGS (Bothast et al 1992;Murthy et al 2005;RFA 2009). The samples selected for this study were chosen to rule out any possible effect of S. maydis infection of corn on ethanol fermentation, and as such, were chosen to represent the whole spectrum of infected corn samples.…”
Section: Effect Of Ear Rot Infection On Ethanol Fermentation and Ddgsmentioning
confidence: 99%